Thermodynamic properties of liquid mixtures. II. Dimethylformamide-water - Cilense, M. [UNESP]; Benedetti, Assis Vicente [UNESP]; Vollet, D. R. [UNESP] (Elsevier, 1983)
The excess enthalpy of mixing of DMF-water was measured at 25° C in the 0-1 molar fraction range. The maximum of heat is developed for a 0.33 DMF molar fraction. The excess partial molar and other excess quantities were also calculated for the DMF-water system at 25° C. The results suggest a strong interaction between DMF and water. © 1983.